Trubarjeva ubeseditev evangelijskih povzetkov v novozaveznih besedilih - Orožen, Martina (Slavistična revija, 2008)
The article fron the syntactic point of view analyzes Trubar's original (rather than translated) texts: summaries of gospel chapters (TE 1555, Mathew's gospel in TT 1581-82) and extensive explications of Sunday and holiday gospels (TR 1558). The author finds an interesting functional duality in wording. In the summaries, there is intentional abbreviation of syntactic structures with omissions of sentence constituents in the basic two-part syntactic pattern and the use of one-part verbal and non-verbal sentence patterns, which still allows understanding of a familiar text. In the explications of the gospels, on the other hand, Trubar used communicatively and stylistically induced expansion of syntanctic structures with repetitions, sometimes triple, in sentence constituents, coordiantion and subordination, which enchance the explicative semantic value and experience of the text. Both syntactic methods of wording as well as the corresponding diversity of the colloquial and terminological lexicon in the first literary decade (1550-1558), attest to the normative refinement of the spoken liturgical style of Slovene.
Keywords: 16.st.; Bible; evangeliji; gospel; knjižni jezik; protestantski pisci; skladnja; Slovene; slovenščina; standard language; sveto pismo; syntax; Trubar, Primož, 1508-1586